Clinical features and survival of gastric cancer patients with DNA mismatch repair deficiency. Issue 4 (11th December 2017) - Ikoma, Naruhiko; Cloyd, Jordan; Badgwell, Brian D.; Agnes, Annamaria; Rodriguez‐Bigas, Miguel; Ajani, Jaffer A.; You, Y. Nancy
Abstract : Patients with germline DNA mismatch repair deficiency (dMMR) have an increased risk of gastric cancer. From our institutional database, we identified 12 patients with germline dMMR gastric cancer. Ten patients (83%) underwent surgical resection, with a 5‐year overall survival rate of 88%. None of the three patients who received preoperative therapy and five patients with recurrent or metastatic disease experienced a significant response to 5‐fluorouracil–based chemotherapy.